2016
DOI: 10.1080/08880018.2016.1225326
|View full text |Cite
|
Sign up to set email alerts
|

Pineal cysts—A benign association with familial retinoblastoma

Abstract: Patients with familial/heritable retinoblastoma (RB) are at increased risk of developing second malignancies throughout life, including a pineoblastoma (trilateral RB [TRB]) in early childhood. Current guidelines recommend regular surveillance brain imaging for those with heritable RB until 5 years of age. The presence of pineal cysts has been reported in patients with RB. Pineal cysts are thought to arise due to focal degeneration of the pineal gland and can be found incidentally. The finding of pineal abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Without treatment, affected pediatric patients generally die within 1–2 years ( 2 ). Invasion and metastasis are the leading causes of death in pediatric patients with RB, making the disease a complex process that involves multiple genes, factors and procedures ( 3 , 4 ). In recent years, enucleation has been excluded from the treatment options for RB, and different treatments are adopted according to the different stages of the tumor, aiming to retain the eyes and their functions ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without treatment, affected pediatric patients generally die within 1–2 years ( 2 ). Invasion and metastasis are the leading causes of death in pediatric patients with RB, making the disease a complex process that involves multiple genes, factors and procedures ( 3 , 4 ). In recent years, enucleation has been excluded from the treatment options for RB, and different treatments are adopted according to the different stages of the tumor, aiming to retain the eyes and their functions ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al ( 19 ) discovered that miR-106b promotes the invasion and migration of esophageal squamous cancer cells in a Kazakh population by downregulating the expression of Smad7. Li et al ( 20 ) reported that miR-106b increases the proliferation, invasion and migration of breast cancer cells by regulating the expression of α-( 1 , 3 )-fucosyltransferase. These studies suggest that miR-106b has varied functions and mechanisms of action in different types of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Pineal tumors are generally smaller than non-pineal tumors in trilateral retinoblastoma (de Jong, Kors, et al, 2014). Benign pineal cysts have also been observed with retinoblastoma (Beck Popovic, Balmer, Maeder, Braganca, & Munier, 2006;Gupta et al, 2016;Karatza, Shields, Flanders, Gonzalez, & Shields, 2006). In rare cases, pineal cysts can transform into malignant tumors, suggesting that they should be monitored over time .…”
Section: Origins and Pathologymentioning
confidence: 99%
“…About 40% to 70% of children with retinoblastoma in the developing countries die, compared with 3% to 5% in the developed nations 6 . The management of retinoblastoma involves multi‐specialty care and involves the modalities of chemotherapy, radiotherapy, and surgery.…”
Section: Introductionmentioning
confidence: 99%
“…5 About 40% to 70% of children with retinoblastoma in the developing countries die, compared with 3% to 5% in the developed nations. 6 The management of retinoblastoma involves multi-specialty care and involves the modalities of chemotherapy, radiotherapy, and surgery. Chemotherapy is used for extraocular tumors to make them amenable to resection and is also used in the adjuvant setting in the presence of high-risk features in intraocular tumors.…”
mentioning
confidence: 99%